Human rights under the Indian constitution - "Mehta, P. L." (New Delhi, 1999)
The authors, by keeping in view the growing significance and popularity of the Human Rights in today's world, have endeavoured to bring home a book on this subject. This book focuses attention on the origin and development of human rights jurisprudence since pre-vedic times with special emphasis on its subsequent up and down journey of different time periods of Indian history. Also it discusses the various constitutional provisions meant to provide human rights to the people of India. Finally, a detailed scrutiny of the judicial decisions of the Indian judiciary has been conducted with a view to know as how far the Indian Courts have succeeded in hammering out a novel human rights jurisprudence in the light of philosophy envisaged in the Constitution of India. The study makes it clear that Indian Courts have shed their character as upholder of the British order and sensitised themselves to the need of doing justice to the large masses of Indian people to whom human rights have been denied by cruel and heartless society for generations. The present work is thus an earnest attempt to throw right on different aspects of human rights jurisprudence with special emphasis on the contribution of Indian courts to make the philosophy of human rights a reality than a myth.
Keywords: Civil rights India-Constitution